Implementation of Work Layout Creation Using Blocplan at SME Sinar Mutiara Karang Serang Village - Syamsudin; Naim, Abu; Sartono; Valentin, Adelia Dwi; Sapriyadi; Hussin, Muhammad; Soesilo, Rahman; Husodo, Purwani (Formosa Journal of Multidisciplinary Research, 2024)
This study investigates how the Sinar Mutiara SMM in the Karang Serang Village  uses the Blocplan to create a working layout. The aim is to improve operational efficiency by optimizing the configuration of working components such as machines and equipment. The Blocplan method is used to analyze data collected from SMEs through observations and interviews. Research results show that using the Blocplan effectively reduces material distances and production time, and also improves space usage. It is hoped that this implementation will be an example for other SMEs to improve efficiency and productivity. In addition, research finds problems such as adaptation to change and resource constraints. For successful implementation in the future, this issue needs to be addressed.